Autosomal Dominant Partial Epilepsies - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
The clinical, electrophysiologic, and genetic characteristics of autosomal dominant partial epilepsy were studied in 71 patients and 33 non-epileptic at-risk family members in 19 European families followed at the Hopital Universitaire de Geneve, Switzerland, and centers in Strasbourg, Paris, Grenoble, Nice, Marseille, Rome, and Pisa.